NLRP6 negatively regulates host defense against polymicrobial sepsis - Ghimire, Laxman; Paudel, Sagar; Le, John; Jin, Liliang; Cai, Shanshan; Bhattarai, Dinesh; Jeyaseelan, Samithamby (Frontiers in Immunology, 2024)
Sepsis remains a major cause of death in Intensive Care Units. Sepsis is a life-threatening multiorgan dysfunction caused by a dysregulated systemic inflammatory response. Pattern recognition receptors, such as TLRs and NLRs contribute to innate immune responses. Upon activation, some NLRs form multimeric protein complexes in the cytoplasm termed "inflammasomes" which induce gasdermin d-mediated pyroptotic cell death and the release of mature forms of IL-1 and IL-18. The NLRP6 inflammasome is documented to be both a positive and a negative regulator of host defense in distinct infectious diseases. However, the role of NLRP6 in polymicrobial sepsis remains elusive. Here, we have used NLRP6 KO mice and human septic spleen samples to examine the role of NLRP6 in host defense in sepsis. NLRP6 KO mice display enhanced survival, reduced bacterial burden in the organs, and reduced cytokine/chemokine production. Co-housed WT and KO mice following sepsis show decreased bacterial burden in the KO mice as observed in singly housed groups. NLRP6 is upregulated in CD3, CD4, and CD8 cells of septic patients and septic mice. The KO mice showed a higher number of CD3, CD4, and CD8 positive T cell subsets and reduced T cell death in the spleen following sepsis. Furthermore, administration of recombinant IL-18, but not IL-1 elicited excessive inflammation and reversed the survival advantages observed in the NLRP6 KO mice. These results unveil NLRP6 as a negative regulator of host defense during sepsis and offers novel insights for the development of new treatment strategies for sepsis.